KONTRIBUSI MINAT BACA DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN MAHASISWA SEMESTER I STIFARM PADANG - Sinta Wahyuni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to describe the following. First, how much is the contribution of reading interest to the reading ability of Semester I students of STIFARM Padang. Second, how much is the contribution of vocabulary mastery to the reading comprehension ability of Semester I Students of STIFARM Padang. Third, how much is the contribution of reading interest and vocabulary mastery together to the reading comprehension ability of Semester I students of STIFARM Padang. This correlational study took the population of Semester I STIFARM Padang students. Sampling was carried out using the purposive sampling technique so that 53 students were obtained as samples. The research instrument is in the form of questionnaires and tests that have been tested for validity and reliability. The results of this study are three, (1) Reading interest gives a significant contribution of 33.9% to the ability to read comprehension because tcount > ttable or 5,110 > 1,684. (2) Vocabulary mastery gave a significant contribution of 35.3% to reading comprehension ability because tcount > ttable or 5.27 > 1,684. (3) Reading interest and vocabulary mastery together gave a significant contribution of 51.8% to reading comprehension ability because tcount > ttable or 26.87 > 3.18.